Challenges and Solutions for the Implementation of Digital-Based Learning in Madrasa: Tantangan dan Solusi Penerapan Pembelajaran Berbasis Digital di Madrasah - Yunus (Transformation of Islamic Management and Education, 2024)
This research aims to find out the role of digital in madrasas. This research is a qualitative research. The data source is primary data from school principals, teachers, and students. Meanwhile, secondary data was taken from documents related to the research. The instruments used in data collection are the researchers themselves who function to determine and select informants as data sources, data analysis, data interpretation, and the instruments in data collection are observation, interviews, and documentation. The results of the study show that the Education Management Information System (SIMDIK) of the Palopo City State Madrasah consists of educational and administrative services by empowering the SIMPATIKA application (Information System for Educators and Education Personnel of the Ministry of Religion), e-learning learning applications, both teachers and students and web-based applications in accepting new students. The implementation of digital-based madrasah management Madrasah Negeri Palopo City focuses on students with the implementation of digital-based learning has many applications and requires the seriousness of teachers to be able to develop various applications for appropriate learning. A digital-based learning evaluation system can be implemented or applied through the RDM Digital application (Madrasah Digital Report).